2017
DOI: 10.3390/ijms18071375
|View full text |Cite
|
Sign up to set email alerts
|

Induction of miR-3648 Upon ER Stress and Its Regulatory Role in Cell Proliferation

Abstract: MicroRNAs (miRNAs) play important roles under multiple cellular conditions including endoplasmic reticulum (ER) stress. We found that miR-3648, a human specific microRNA, was induced under ER stress. Moreover, Adenomatous polyposis coli 2 (APC2), a tumor suppressor and a negative regulator of Wnt signaling, was found to be the direct target of miR-3648. Levels of APC2 were downregulated when cells were under ER stress or after overexpressing miR-3648. Inhibition of miR-3648 by antagomir increased APC2 levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The known functions of these 44 mature miRNAs in cellular proliferation and cancer as well as their targets are listed in the Supplemental Table S4. Among them, miR-31-5p (Zheng et al 2015) and miR-3648 (Rashid et al 2017) have previously been shown to promote the proliferation of HeLa cells, and miR-31-5p has also been shown to act as an oncogene in cervical cancer (Rao et al 2012;Wang et al 2014a;Zheng et al 2015).…”
Section: Identification Of Fitness-associated Mirnasmentioning
confidence: 99%
“…The known functions of these 44 mature miRNAs in cellular proliferation and cancer as well as their targets are listed in the Supplemental Table S4. Among them, miR-31-5p (Zheng et al 2015) and miR-3648 (Rashid et al 2017) have previously been shown to promote the proliferation of HeLa cells, and miR-31-5p has also been shown to act as an oncogene in cervical cancer (Rao et al 2012;Wang et al 2014a;Zheng et al 2015).…”
Section: Identification Of Fitness-associated Mirnasmentioning
confidence: 99%
“…To understand biological functions, miRNAs exhibiting differential expression above 2 logs fold of magnitude were selected. The development of NSCLC was associated with an increase of molecules associated with endoplasmic reticulum (ER) stress [ 28 ] - hsa-miR-3648 (up 2.08 folds) and TNF-α, IL-6 suppression [ 29 ] - hsa-miR-4488 (up 3.49 folds), and decrease of one that is known to regulate glioma cell invasiveness and the release of extracellular vesicles - hsa-miR-5096 (down 3.02 folds) [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In SCLC, several molecules were elevated: the marker of breast cancer chemotherapy resistance and self-renewal capability - hsa-miR-4508 (up 2.07 folds) [ 33 ], serum-based biomarker for muscle-invasive bladder cancer survival [ 34 ] - hsa-miR-486-3p (up 2.16 folds), the noted above as an indicator of the ER stress [ 28 ] and a suppressor of antitumor adenomatous polyposis coli 2 (APC2) [ 28 ] - hsa-miR-3648 (up 2.2 folds), a critical β-catenin-activated prometastatic miRNA and a negative regulator of the metastasis suppressors RhoGDI1 and ALCAM [ 35 ] - hsa-miR-483-5p (up 3.16 folds), apoptosis suppressing [ 36 ] - hsa-miR-1228-5p (up 3.29 folds). The hsa-miR-5096 (down 2.76 folds) of unknown function was downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs are known to play pivotal roles in myriad of cellular functions ranging from development to disease and response to endogenous or exogenous stimuli. [31][32][33][34][35] To assess the involvement of a miRNA in a biological process, computational methods and molecular biology approaches are routinely used. Computational methods generally rely on phylogenetically conserved miRNA binding sites in the target gene and free energy of binding.…”
Section: Discussionmentioning
confidence: 99%
“…37 Similarly, miR-3648 targeted only one gene in contrast to 13 predicted targets. 34 Therefore, experimental approach to identify true miRNA targets is indispensable. Biochemical approaches such as AGO2-IP, high-throughput sequencing coupled with UV cross-linking and immunoprecipitation (HITS-CLIP), photoactivatable-ribonucleoside-enhanced cross-linking and immunoprecipitation (PAR-CLIP), 3 0 end biotin-tagged miRNA, miRNP immunopurification, or a recently developed screening system to identify miRNA targets are available.…”
Section: Discussionmentioning
confidence: 99%